Positive Discipline Approaches and Students’ Behaviour in GovernmentAided Secondary Schools in Sheema Municipality, Uganda - Waiswa, Mark Micheal; Mutungi, Alex; Mugizi, Wilson; Ludigo, Harriet (East African Journal of Education Studies, 2024)
This study examined the relationship between positive discipline approaches and students’ behaviour in secondary schools in Sheema Municipality in southwestern Uganda. Positive discipline approaches were looked at in terms of guidance and counselling, positive reinforcement and role modelling in relation to students' behaviours. This cross-sectional study involved a sample of 343 students. Data were collected from the students using a self-administered questionnaire. Partial least square structural equation modelling (PLS-SEM) was used to carry out data analysis. The findings indicated that the measurement model was good and structural equation model results revealed that guidance counselling and positive reinforcement positively and significantly related to students’ behaviour. However, role modelling is positively but insignificantly related to students’ behaviour. The results imply that while guidance counselling and positive reinforcement are essential factors for promoting students’ behaviour, role modelling is not. Therefore, it was recommended that school administrators and teachers should emphasise providing guidance counselling and positive reinforcement to students as they handle them while role modelling should not be prioritised